A multi-criteria, network analytic approach to war game participant selection. (April 2016) - Bastian, Nathaniel D; Boguchwal, Louis; Langhans, Zachary; Evans, Daniel
A critical component of the military war game planning process is selecting who should participate, as these participants heavily influence war game outcomes. These outcomes directly impact both strategic and operational decision-making and defense planning, shaping both future defense policy and budget. In this paper, we propose a novel team selection algorithm and decision-support tool combining methods from multiple criteria decision analysis and network analytics to select and visualize a group of war game participants. This method accounts for the diverse requirements of the decision-maker. The results are not only applicable to war games, but also to any team selection domain, such as employee hiring and college admissions.